Por que somos decadentes : afirmação e negação da vida segundo Nietzsche - Evaldo Sampaio da Silva (2009)
The aim of this work is to think the presuppositions and implications of a philosophy’s original subject, that is, “which is the best way to live?”, on the context of Friedrich Nietzsche’s work. It is hoped to show that Nietzsche’s reflexion on moral prejudices reaches its fullness in an investigation of the ascension and decadence of the vital drives. This research indicate that as much the appropriate inquiry as the eventual answers on the superior or inferior forms of live are related to a critic of the moral judgments and constitute the nucleus of Nietzsche’s philosophical ambitions. It is justified the relevance and consistence of the Nietzsche’s theory of decadence for an exam of his self-interpretation by an analysis guided primarily second the structural method. After, it is exposed how his self interpretation is an expression of an internal movement of Nietzsche’s reflexions which conduct him to a moral or extra-moral philosophy. Finally, for an analysis of his project of the revaluation of all values, it is determined that the affirmation and the denial of life constitute the way to establish which are the superior or inferior ways of living and, with that, why we are decadent.